Navigating the Global Economic Landscape of Dialysis: A Summary of Expert Opinions from The 4th International Congress of Chinese Nephrologists - Philip Kam-Tao Li; Jack Kit-Chung Ng; Guang-yan Cai; Wei Chen; Kai Ming Chow; Stanley Fan; John Cijiang He; Lai Seong Hooi; York Pei; Boon Wee Teo; Muh Geot Wong; I-Wen Wu; et al. (Karger Publishers, 2024)
Background: Chronic kidney disease (CKD) continues to be a significant global public health issue. The escalating burden of CKD is probably driven by the aging population and the rising prevalence of diabetes. CKD not only adversely impacts an individual's health and well-being, but also poses significant challenge on the economy of the society. Summary: Experts from ten countries and regions around the world (Australia, Canada, China, Hong Kong, Malaysia, New Zealand, Singapore, Taiwan, United Kingdom, and United States) convened in the 4th International Congress of Chinese Nephrologists on December 1, 2023 to discuss the global dialysis burden. Although the cost of kidney replacement therapy (KRT) accounts for 2-3% of total healthcare expenditure in developed countries, patients with end stage kidney disease (ESKD) only represent a small percentage (<0.5%) of the population. Importantly, the economic impact of ESKD is not limited to direct medical costs, but extends to indirect societal costs, such as productivity loss by patients and caregivers. Primary prevention of CKD, early screening and treatment to delay progression to ESKD (where treatment costs rise dramatically), and utilization of home-based dialysis therapy (including peritoneal dialysis and home hemodialysis) shall be implemented as part of cost-containment strategy. Kidney transplant provides better outcomes than dialysis and is cost-effective in long run, whereas conservative kidney management should be considered for elderly frail patients. Key Messages: Implementation of preventive measures and cost-effective treatment strategies are the cornerstone to combat the global CKD epidemic.